Soybean rust situation in western Maharashtra during 2002 to 2005 - and A.M. TIRMALI, G.G. KHOT*, V.S. PATIL, B.P. KURUNDKAR, V.S. SHINDE, S.R. LOHATE (Indian Phytopathology, 2009)
Survey was conducted during the rainy season from 2002 to 2005 from Sangli, Kolhapur, and Satara districts of Maharashtra state and border areas of Karnataka to know the situation of soybean rust. Results indicated that disease is widely prevalent in these areas. It appeared from second week of July during 2004 and from August onwards during other years. Incidence of rust varied from 0-100 percent during individual years. First infection was noticed at Dattawad, Bubnal and Shirdwad villages of Shirol talukas of Kolhapur districts. This area adjoining to Krishna river belt seems favourable for early infection from where disease spread to Sangli, Satara districts and adjoining area.